Models of Care Parents and Their Effects on Developing Emotional Intelligence - Muhammad Anas; Abdul Saman (Universitas Negeri Makassar, 2017)
This study aims to describe the model parenting, teenage emotional intelligence level, and models of care that tend to be positively and negatively affect adolescent emotional intelligence. Subjects were high school students Makassar. Samples were students of SMAN 3, 4, 5, 12, National High School and High School PGRI totaled 353 students. The instrument used in this study was a questionnaire. Data were analyzed using descriptive and inferential techniques through Amos and SPSS programs. The results showed: (1) in general adolescents in the city of Makassar have emotional intelligence in the category is quite high, especially in the aspect of recognizing emotions, empathy, and self-motivation; (2) patterns applied pengsuhan parents are more likely to vary, but in general parenting experienced by adolescents is parenting-child communication and parental nurturance pattern. (3) patterns of parenting to significantly influence the development of adolescent emotional intelligence.